2012
DOI: 10.7205/milmed-d-12-00019
|View full text |Cite
|
Sign up to set email alerts
|

Deployment Risk Factors and Postdeployment Health Profiles Associated With Traumatic Brain Injury in Heavy Drinking Veterans

Abstract: Along with post-traumatic stress disorder (PTSD), mild traumatic brain injury (mTBI) is considered one of the “signature wounds” of combat operations in Iraq (Operation Iraqi Freedom [OIF]) and Afghanistan (Operation Enduring Freedom [OEF]), but the role of mTBI in the clinical profiles of Veterans with other comorbid forms of postdeployment psychopathology is poorly understood. The current study explored the deployment risk and postdeployment health profiles of heavy drinking OIF and OEF Veterans as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…147 The increased prevalence of PTSD is important because PTSD can worsen outcomes in people with mTBI. For example, comorbid PTSD and TBI result in higher prevalence of cognitive and functional impairments 148 including reduced attentional performance, 149 more frequent and severe headaches, 150 other painrelated complaints, mood disorders, other anxiety disorders, and substance use disorders, 13,151,152 than either condition alone. [153][154][155] Sleep disturbances are common in both PTSD and mTBI and are more common among those with comorbid PTSD and mTBI than among those with either condition alone.…”
Section: Sleep and Ptsd In Mtbimentioning
confidence: 99%
“…147 The increased prevalence of PTSD is important because PTSD can worsen outcomes in people with mTBI. For example, comorbid PTSD and TBI result in higher prevalence of cognitive and functional impairments 148 including reduced attentional performance, 149 more frequent and severe headaches, 150 other painrelated complaints, mood disorders, other anxiety disorders, and substance use disorders, 13,151,152 than either condition alone. [153][154][155] Sleep disturbances are common in both PTSD and mTBI and are more common among those with comorbid PTSD and mTBI than among those with either condition alone.…”
Section: Sleep and Ptsd In Mtbimentioning
confidence: 99%
“…The etiology that contributes to a TBI may be the same that contributes to the development of PTSD. 3,26-30 Hence, it is logical that TBI and PTSD are correlated among those returning from OEF/OIF. 8,31-34 Studies have found that mild TBI, defined as an alteration or loss of consciousness of up to 30 minutes after an injury event, 35,36 may increase the likelihood of developing PTSD, 31,37 or complicate recovery from PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Using alcohol (or other stimulants) with the aim of easing the effects of experiences of a traumatic nature constitutes a problem for a multitude of people who are involved in actions that endanger their safety, to a large extent soldiers and non-professional veterans of combat action [4]. Searching for relief and improvement of self-esteem by means of alcohol is treated as a non-constructive strategy in easing the psycho-physiological effects of stress, which improves self-esteem only for a brief period, after which it deepens the existing health, financial and social problems [5].…”
mentioning
confidence: 99%
“…Research illustrates that in terms of people who want to reduce the unpleasant experiences, there is a risk of developing an addiction [4,6]. The relation between health and coping with long-term stress and pain is widely analysed and widely documented in psychoneuroimmunology [8,9].…”
mentioning
confidence: 99%